Single Center Experience With Pediatric Patients With GATA2 Deficiency - Galina Ovsyannikova; Anna Pavlova; Ekaterina Deordieva; Elena Raykina; Alexey Pshonkin; Alexey Maschan; Michael Maschan (Frontiers Media S.A., 2022)
GATA2 deficiency is one of the most common predisposing conditions for MDS in young individuals. It is characterized by autosomal dominant inheritance and a high rate of de novo mutations. Here we describe the clinical phenotype and hematological presentation of 10 pediatric patients with GATA2 deficiency presented to the Dmitry Rogachev Center between 2013 and 2020. All patients had been referred for neutropenia or suspected aplastic anemia. While some patients presented with an immunological phenotype, others displayed monosomy 7 and MDS. The clinical presentation with MDS in infancy and the constitutional phenotypes in our patients underline the great variability in clinical manifestation. Careful description of cohorts with GATA2 deficiency from different countries and genetic backgrounds will help to unravel the enormous heterogeneity of this recently discovered genetic disorder.